Formation of Linear Oligomers in Solid Electrolyte Interphase via Two‐Electron Reduction of Ethylene Carbonate. Issue 5 (17th February 2022) - Liu, Yue; Wu, Yu; Sun, Qintao; Ma, Bingyun; Yu, Peiping; Xu, Liang; Xie, Miao; Yang, Hao; Cheng, Tao
Abstract: Solid electrolyte interphase (SEI) plays a significant role in enhancing the stability and durability of lithium metal batteries (LMBs) by separating highly reactive lithium metal anode (LMA) from the electrolyte to avoid continuous degradation. However, the underlying reaction mechanism is still far from clear. Herein, a hybrid ab initio and reactive force field (HAIR) method is employed to extend the ab initio molecular dynamics (AIMD) to 1 ns, which provides crystal information about the reaction mechanism of elementary reactions that can explain the components and morphology evolution of SEI formation. Specifically, HAIR simulation confirms the two‐electron (2 e – ) reduction of ethylene carbonate (EC) by releasing CO and CO2, agreeing with phenomenal experiment observation. As the unsaturated intermediates accumulate, polymerization reactions occur, producing linear polyethylene oxide (PEO), Li2 OCO2 CH2 CH2, Li2 OCO2 (CH2 )4, etc., which regulate the formation of outer organic layer (OOL) that consists of linear polyethylene oxide (PEO), Li2 OCO2 CH2 CH2, Li2 OCO2 (CH2 )4, etc., and the inner inorganic layer (IIL) mainly consists of LiF and Li2 O. Simulations at low concentration (LC, 1M) and high concentration (HC, 5M) reveal significantly different reaction pathways when HC electrolyte can significantly promote the formation of homogenous LiF that has been regarded as an important component to facilitate robust SEI. Abstract : The solid electrolyte interphase (SEI) is important for improving the stability and endurance of lithium metal batteries. The underlying reaction mechanism, however, is yet unknown. Simulated chemical pathways at low concentration (LC, 1 m LiTFSI) and high concentration (HC, 5 m LiTFSI) show considerable differences, when HC electrolyte can significantly promote the formation of homogenous LiF.